A web repository to describe and execute shape oriented workflows. Issue 5 (2nd September 2016) - Attene, Marco; Cabiddu, Daniela; Gagliardo, Stefano; Giannini, Franca; Monti, Marina
ABSTRACT: The effective use of advanced tools and geometric models across different applications frequently requires model processing to satisfy the application requirements. Besides being time consuming processes, these model adaptations normally employ advanced tools that need specific knowledge for their proper usage. Therefore, it is frequently difficult understanding which tools and operations better fit with the specific purposes. This paper presents the capabilities of the Visualization Virtual Service (VVS) infrastructure for the creation and retrieval of shape processing workflows either to describe best practice process pipelines or to allow running sequences of web services. GRAPHICAL ABSTRACT: